Association Between Hindfoot Alignment and First Metatarsal Rotation. (January 2022) - Bakshi, Neil; Steadman, Jesse; Philippi, Matthew; Arena, Christopher; Leake, Richard; Saltzman, Charles L.; Barg, Alexej
Background: The association between forefoot and hindfoot position for planus and cavus feet is fundamental to the treatment of these deformities. However, no studies have evaluated the association between hindfoot alignment and first metatarsal (M1) axial rotation. Understanding this possible relationship may help to understand the deformity and improve patient care. The purpose of this study is to determine a correlation between hindfoot alignment and metatarsal rotation as assessed by weightbearing computed tomography (WBCT). Methods: Patients who underwent weightbearing plain radiography (WBPR) and WBCT between 2015 and 2018 were evaluated. Hindfoot alignment was measured with the calcaneal moment arm (CMA). M1 rotation was measured using the Kim and Saltzman angles. Patient subgroups were created according to the severity of valgus/varus hindfoot alignment. Statistical analyses were performed to evaluate for association between variables. Results: Among the 196 patient feet included in the study, the average CMA was 6.0 ± 16.2 mm. The average Kim and Saltzman angles were 7.7 ± 12.9 degrees and 2.8 ± 13.1 degrees, respectively. The average Meary angle was 182.0 ± 11.9 degrees. A moderately strong association was found between the CMA and the Saltzman ( r = 0.641, P < .01) and Kim angles ( r = 0.615, P < .01). Hindfoot valgus was associated with M1 pronation and hindfoot varus with M1 supination. Additionally, inverse relationships between the Meary angle and the Saltzman ( r = −0.600, P < .01) and Kim angles ( r = −0.529, P < .01) were identified. Conclusion: In this well-defined cohort, we found substantial correlation between hindfoot alignment and M1 rotation. Hindfoot valgus was associated with M1 pronation, and hindfoot varus was associated with M1 supination. Surgeons correcting cavovarus/planovalgus deformities should be aware of this association and evaluate the need for first-ray derotation. Level of Evidence: Level III, retrospective cohort study.